Classificação imunofenotípica do linfoma de gatos domésticos e sua correlação com o vírus da leucemia felina - Dayse Helena Lages da Silva (2019)
Lymphoma is the most common neoplasm in cats, presenting several anatomical forms, the most common being gastrointestinal. However, involvement of the gammaretrovirus may predispose the presentation of other anatomical forms such as the mediastinal and multicentric. The objective of this work was to conduct a retrospective study of feline lymphoma and to correlate the anatomical form, the immunophenotype with the presence of feline leukemia virus proviral DNA (FeLV), for which 56 cases were evaluated. The most common form of lymphoma was gastrointestinal. There was no significant difference in the proportion between T-cell (28) and B-cell lymphoma (26). Using DNA extracted from paraffinized tissue from 29 cats, 24 positive for FeLV proviral DNA were obtained through semi nested PCR. The multicentric anatomical form had a higher percentage (37.5%) of the presence of FeLV proviral DNA, followed by mediastinal. The immunophenotype that had the highest correlation with the presence of the virus was T-cell lymphoma (50%). Apparently in Brazil, there is a high relation between the lymphoma and the presence of the proviral DNA of FeLV